The Importance of Breakfast in Enhancing Students' Focus at School - Nurul Widad Fitri Muhammad; Nur Aina Mardhiah Che Rahim; Amrina Rasyada Kamaruzaman; Noor Fatimah Mujahid; Khairulnazrin Nasir (Rabbanica: Journal of Revealed Knowledge, 2023)
One of the critical components in improving students' focus at school is a healthy breakfast. Students who skip breakfast will become hungry, which can disrupt their learning. Islam, as a complete faith, emphasises eating healthy meals. From an Islamic perspective, this article will suggest eating a healthy breakfast to improve students' focus in the classroom. Research on the association between eating breakfast and students' attention span has received much attention. However, studies on the relationship between eating a nutritious breakfast and being attentive while studying according to Islamic principles are still insufficient. This study adopted a qualitative methodology using library research, and information was acquired through books, documents, and journal articles from earlier research. The definition, concept, and required materials of the foods, breakfast, Islamic principle, and focus were elaborated by descriptive analysis of the content, and they were gathered following the topic. The results demonstrate that eating a healthy breakfast, a combination of carbohydrates, proteins and vegetables, does help students focus better in class. Furthermore, it has been shown that eating healthy foods, as mentioned in the Quran and Hadith, improves students' quality of life. In conclusion, this information can be used as a benchmark by the relevant party to boost student achievement.